2012
DOI: 10.1111/j.1526-4610.2011.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan Inhibits TRPV1 Channels in Trigeminal Neurons

Abstract: Objective To understand a possible role for transient potential receptor vanilloid 1 (TRPV1) ion channels in sumatriptan relief of pain mediated by trigeminal nociceptors. Background TRPV1 channels are expressed in small nociceptive sensory neurons. In dorsal root ganglia (DRG), TRPV1-containing nociceptors mediate certain types of inflammatory pain. Neurogenic inflammation of cerebral dura and blood vessels in the trigeminal nociceptive system is thought to be important in migraine pain, but the ion channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…This high level of co-localization is consistent with reports that TRPV1 receptor activation in the dura stimulates CGRP release and subsequent vasodilatation [44][45][46]. Most studies report the presence of TRPV1 in presynaptic terminals of TNC [43,47], but see [48]. TRPV1 has also been detected in arteriole smooth muscle in the dura [43], albeit at low abundance [49].…”
Section: Trpv1 Localizationsupporting
confidence: 89%
See 3 more Smart Citations
“…This high level of co-localization is consistent with reports that TRPV1 receptor activation in the dura stimulates CGRP release and subsequent vasodilatation [44][45][46]. Most studies report the presence of TRPV1 in presynaptic terminals of TNC [43,47], but see [48]. TRPV1 has also been detected in arteriole smooth muscle in the dura [43], albeit at low abundance [49].…”
Section: Trpv1 Localizationsupporting
confidence: 89%
“…TRPV1 is widely expressed in the anatomical substrates of migraine, particularly in soma of the trigeminal ganglion, nerve fibers, in central terminals in the TNC and in peripheral terminals within the dura [29,30,42,43]. Although previous studies had demonstrated the occurrence of TRPV1 receptors in the dura, the origin of the TRPV1 protein was not known.…”
Section: Trpv1 Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Capsaicin evokes CGRP release from dural tissue via TRPV1 activation, which in turn leads to CGRP-dependent vasodilatation (Eltorp et al, 2000). Furthermore, in trigeminal nucleus caudalis slices, capsaicin produces repetitive action potential formation and subsequent CGRP release that is inhibited by the antimigraine drug sumatriptan (Evans et al, 2012). Importantly, in the cat, application of the inflammatory soup to the dura increased blood flow and led to neuronal sensitization to mechanical stimuli; these responses were reversed by the TRPV1 antagonist SB705498 (Lambert et al, 2009).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%